2021
DOI: 10.3390/jcm10194596
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Impact of Economic Downturn and Loneliness on Psychological Distress: Triple Crises of COVID-19 Pandemic

Abstract: Background: The COVID-19 crisis poses global mental health and global economy challenges. However, there is a lack of longitudinal research investigating whether financial instability and social disruption may increase the risk of developing mental health problems over time that may potentially outlast the pandemic. Methods: We conducted an online survey for members of the general population (n = 2703) in Germany during the twelve months spanning from April 2020 to March 2021. We investigated the development o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 48 publications
(65 reference statements)
1
27
0
Order By: Relevance
“…Other studies reported increased frequency of unhealthy behaviours and domestic violence [ 65 ] as well as increased distress [ 51 , 53 , 66 ]. On the other hand, a growing importance of religious practices was reported by Bentzen in a study conducted in 95 countries [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported increased frequency of unhealthy behaviours and domestic violence [ 65 ] as well as increased distress [ 51 , 53 , 66 ]. On the other hand, a growing importance of religious practices was reported by Bentzen in a study conducted in 95 countries [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fewer social resources before containment (e.g., lower levels of social capital, perceived social support, and neighbourhood relationships) were also associated with more negative mental health effects such as depression and anxiety during containment [ 145 , 147 , 148 ]. The association between low income and loneliness with depression and anxiety is especially critical during pandemic-related social isolation, income disparity, and loss of employment [ 146 , 149 ]. Health care workers can be affected by social stigma in addition to the risk of infections due to their potential exposure to contagious patients and may be another group with higher probability of negative psychological outcomes [ 8 ].…”
Section: Social Isolation and Discrimination In Humansmentioning
confidence: 99%
“…We limited the number of control variables to build parsimonious models, taking the relatively small sample size relative to the complexity of the models. We chose age and social economic hardship as these have been found to effect loneliness in an overwhelming amount of studies on mental health among the general population during the pandemic [ 4 , 59 , 60 , 61 ], as well as before the pandemic [ 62 ].…”
Section: Methodsmentioning
confidence: 99%